Green synthesis of silver nanoparticles by Pisum sativum L. (pea) pod against multidrug resistant foodborne pathogens - Khaloud Mohammed Alarjani; Dina Huessien; Rabab Ahmed Rasheed; M. Kalaiyarasi (Journal of King Saud University: Science, 2022)
The consumption of foods contaminated with various foodborne organisms such as, viruses, fungi and bacteria are recognized as the important sources of foodborne illness in animals and humans. Multidrug resistant foodborne bacteria increased morbidity, mortality rates, and severe economic loss and associated with prolong hospitalization. The development of natural and novel antibacterial agent is much needed as there is an increasing concern on multidrug resistant bacteria. This study aimed to synthesize silver nanoparticles using aqeous Pisum sativum L. (pea) pod extract and to characterize the nanoparticles. It was further used on various drug resistant foodborne bacterial pathogens and antimicrobial activity was determined. The synergistic antibacterial activity, antioxidant activity and biocompatibility were also assessed. Green synthesized nanoparticles applied in this study were synthesized using aqueous P. sativum L. (pea) pod extract with particle size 30 nm. The green synthesized silver nanoparticles showed antimicrobial activity against Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 25922, Enterococcus faecalis ATCC 700802, Streptococcus gordonii ATCC 49818, Staphylococcus aureus (MRSA) ATCC 4330 and Staphylococcus aureus ATCC 25923. Among the pathogenic bacterial strains, silver nanoparticles were highly active against S. aureus ATCC 25923 than other bacterial strains (22 ± 2 mm). The antibacterial activity varied between 15 ± 2 mm and 22 ± 2 mm diameter zone of inhibition. The MIC value of the nanoparticles ranged from 6.25 µg/mL to 75 µg/mL and MBC value ranged from 50 µg/mL to 150 µg/mL. The green synthesized nanoparticles showed antioxidant potential. Normal fibroblast cell lines (L-929) was used to test the cytotoxic activity and the increased IC50 value (750.5 ± 5.5 μg/mL) indicated good biological compatibility. The present findings revealed that green synthesized silver nanoparticles exhibited potent activity against various food borne pathogenic bacteria. These nanoparticles might be well developed as novel antibacterial substances for the treatment of food borne multidrug resistant bacterial infection.